1969
DOI: 10.2466/pms.1969.29.2.555
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Dimensions of Cerebrovascular Insufficiency

Abstract: 129 patients with cerebrovascular insufficiency (CVI) were studied on 43 scores from psychological tests of intellectual functioning and 42 scores from physiological measures. BC TRY cluster analysis of 35 psychological variables yielded 3 strong dimensions labeled verbal, visual-motor, and numerical, as well as a weaker dimension labeled attention. These 4 dimensions accounted for 91% of the communality among the 35 psychological variables. The dimensions were fairly highly intercorrelated, and correlated sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1972
1972
1977
1977

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Fields (1971) found the WAIS and WMS to be highly correlated (.83), and Ivinskis et al (1971) questioned whether the WMS constituted a memory scale, in light of its relationship with the Wechsler Intelligence Scale for Children (WISC) and WAIS. Vitale et al (1969) found the WMS MQ to be clustered with some WAIS tests. Dujovne and Levy (1971) found their first factors to be related to intelligence, but their second and third factors, loading on the pairedassociate tasks, appeared not to be related in normals or patients.…”
Section: Wechsler Memory Scalementioning
confidence: 94%
See 2 more Smart Citations
“…Fields (1971) found the WAIS and WMS to be highly correlated (.83), and Ivinskis et al (1971) questioned whether the WMS constituted a memory scale, in light of its relationship with the Wechsler Intelligence Scale for Children (WISC) and WAIS. Vitale et al (1969) found the WMS MQ to be clustered with some WAIS tests. Dujovne and Levy (1971) found their first factors to be related to intelligence, but their second and third factors, loading on the pairedassociate tasks, appeared not to be related in normals or patients.…”
Section: Wechsler Memory Scalementioning
confidence: 94%
“…Many of these references added little to our understanding of the scale itself. In some studies, the intent was to measure the effects of certain diseases or of medical interventions (Cameron, Sved, Solyom, Wainrib, & Barik, 1963;Kastl, Daroff, & Blocker, 1968;Levy, 1968;Mensh, Schwartz, Matarazzo, & Matarazzo, 19S2;Uecker, French, & Johnson, 1954;Victor, Talland, & Adams, 1959;Vitale, Steinhelber, Drake, & Dahlgren, 1969;Zamora & Kaelbling, 1965). With other studies, the WMS was included in a large battery of psychological tests of intellectual functioning (Dixon, 1965;Gilberstadt, 1968;Logue, Durward, Pratt, Piercy, & Nixon, 1968;Vitale et al, 1969).…”
Section: Wechsler Memory Scalementioning
confidence: 99%
See 1 more Smart Citation
“…It has five subscales which measure responsiveness, verbal ability, numerical ability, visual-motor ability, and orientation and attention. A recent cluster analytic study included this test as one of a battery (Vitale & Steinhelber, 1969). In addition, it has been used successfully in the evaluation of patients with extracranial occlusive disease (Drake et al, 1970).…”
Section: And the 7 Try On Cluster Analyzed Scales (Try On 1966) Label...mentioning
confidence: 99%